Pengaruh Kompetensi, Independensi dan Situasi Audit Terhadap Skeptisisme Profesional Auditor (Studi Kasus Pada Kantor Akuntan Publik di Kota Malang) - Mokhammad Ali Alfian Ridho; Maslichah Maslichah; Irma Hidayati (Universitas Islam Malang, 2023)
Professional skepticism is discipline that includes a mind that always questions and critically evaluates audit evidence. This study aims to determine the influence of competence, independence and audit situation on auditor professional skepticism both simultaneously and partially. This research method is classified as correlational by using a quantitative approach. The data used is primary data using questionnaires. The population in this study is auditors who work in Public Accounting Firms (KAP) in Malang city not limited by positions which include partners, managers, senior and junior auditors with a minimum of 1 year of work. Sampling using purposive sampling, data obtained as many as 42 respondents. Data analysis using multiple linear regression. Meanwhile, data processing uses IBM SPSS 22. The results of the analysis showed that competence had a positive and significant effect on auditor professional skepticism, independence and audit situation had no effect on auditor professional skepticism.Keyword : Competence, independence, audit situation and auditor professional skepticism